Contribution to the Knowledge of the Genus Linda Thomson, 1864 (Part I), with the Description of Linda (Linda) subatricornis n. sp. from China (Coleoptera, Cerambycidae, Lamiinae) - Mei-Ying Lin; Xing-Ke Yang (Psyche: A Journal of Entomology)
Linda (Linda) subatricornis n. sp is described from Sichuan (holotype locality), Fujian, Shaanxi, Hebei, Ningxia of China. It is separated from the most similar species L. atricornis Pic by differences in genitalia and antennal insertions. Detailed descriptions, photographs of habitus and genitalia, distribution of the two sibling species and short discussion on the related species are presented.